Japan: Diagnosis and Management of Stevens-Johnson Syndrome/Toxic Epidermal Necrolysis With Severe Ocular Complications - Sotozono, Chie; Ueta, Mayumi; Kinoshita, Shigeru (Frontiers in Medicine, 2021)
In 2005, the 'Japanese Research Committee on Severe Cutaneous Adverse Reaction' (J-SCAR) presented the official 'Diagnostic Criteria' for SJS/TEN, and the specific ocular findings are included in this very important criteria. In SJS/TEN cases involving ocular disorder, conjunctivitis often occurs prior to the onset of the high fever. In a Japanese survey, ocular involvement was observed in 77% of the cases, and the incidence of ocular sequelae increased depending on the score of the acute ocular severity findings. Pseudo-membrane formation and epithelial defects are considered to be high-risk signs of ocular sequelae. At the chronic stage, limbal stem cell deficiency, visual disturbance, and severe dryness of the ocular surface are the primary disease characteristics. In 2002, we started performing Cultivated Oral Mucosal Epithelial Transplantation (COMET) for the treatment of severe ocular disorders, including SJS/TEN. As an additional treatment method, we developed a new type of rigid contact lens (CL) that is 13 to 14.0-mm in diameter, known as the “Limbal Rigid Contact Lens (Limbal CL)”. Our Limbal Rigid CL greatly enhances the postoperative outcome of COMET. The detection rate of ocular surface bacteria is high in SJS/TEN cases. Thus, appropriate use of topical antibiotics reduces the risk of ocular surface inflammation. Moreover, rebamipide is an ophthalmic solution for dry eye that was developed in Japan, and it also has the effect of suppressing ocular surface inflammation. From disease onset until the chronic stage, the control of inflammation and stem cell loss is key to successfully treating eyes afflicted with SJS/TEN.